INTERACTION OF TIN-CHLORIDE COMPLEXES OF PALLADIUM WITH SILICA GELS, WHICH CONTAIN SULFUR-CONTAINING FUNCTIONAL GROUPS: UDC 543.183.5:546.55:546.98 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
The sorption of Pd (II) tin-chloride complexes on silica gel impregnated by polyhexamethyleneguanidine and following synthesis of sorbents' on its basis containing complexing functional groups with sulfur is researched. It is shown, that the palladium quantitative extraction on the given sorbents from 1–4 M HCl solutions is possible.
Keywords: -